(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The present study has been carried out to find out the relationship between Teacher Burnout in terms of emotional exhaustion, personal accomplishment and depersonalization and Teacher effectiveness among High school teachers in West Bengal. This study is Correctional Study. Population of the study comprises of the high school teachers of West Bengal. Out of the population a sample of 100 school teachers of Paschim Medinipur district have been used for data collection. The Maslach Burnout Inventory (MBI) developed by Maslach and Jackson, 1981 and Teacher Effectiveness Scale devised by Gulzar Ahmad Dar and Dr. P. Ponraj have been used for data collection. Collected data were analyzed with simple Mean, Standard Deviation and Pearson Correlation. The study reveals that there is a positive correlation between Personal Accomplishment component of Teacher Burnout and Teacher Effectiveness, which implies that with reducing Personal Accomplishment their Teacher Effectiveness, is reduced and there is a negative correlation -between Depersonalization component of Teacher Burnout and Teacher Effectiveness.